Saadia vs. Rashi: On the Shift from Meaning-Maximalism to Meaning-Minimalism in Medieval Biblical Lexicology - Steiner, Richard C. (The Jewish quarterly review, 1998)
Saadia Gaon and Rashi held very different views concerning the task of the lexicographer. Saadia believed that the lexicographer must not limit himself to listing the common, well-attested meanings of a word; he has a duty to posit additional meanings as a means of resolving contradictions and producing smooth, coherent readings. Rashi felt that words have only one basic meaning from which all of the contextual meanings are derived, and that the task of the lexicographer is to find that meaning. Saadia's view was shaped by Muslim intellectual traditions. Rashi's view bears some resemblance to that of an anonymous 11th-century French speculative grammarian, but its roots are in rabbinic literature. Other exegetes cited in this article (the Masoretes, David al-Fāsī, Menaḥem ben Saruq, Jonah ibn Janāḥ, Joseph Qara, Abraham ibn Ezra, David Qimḥi, Joseph ibn Kaspi) have not been studied systematically, but the evidence gathered up to now suggests that the difference between Saadia Gaon and Rashi is part of a more general shift from meaning-maximalism to meaning-minimalism in medieval biblical lexicology--a shift which occurred independently in Spain and France.